Manipulation of pyrophosphate fructose 6-phosphate 1-phosphotransferase activity in sugarcane - Groenewald, Jan-Hendrik (Stellenbosch : University of Stellenbosch, 2006)
Thesis (PhD (Genetics. Plant Biotechnology))--University of Stellenbosch, 2006.